2014
DOI: 10.1002/glia.22754
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐sequencing reveals oligodendrocyte and neuronal transcripts in microglia relevant to central nervous system disease

Abstract: Expression profiling of distinct central nervous system (CNS) cell populations has been employed to facilitate disease classification and to provide insights into the molecular basis of brain pathology. One important cell type implicated in a wide variety of CNS disease states is the resident brain macrophage (microglia). In these studies, microglia are often isolated from dissociated brain tissue by flow sorting procedures (FACS) or from postnatal glial cultures by mechanic isolation. Given the highly dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 67 publications
3
33
0
Order By: Relevance
“…S1C) in our microglial isolations due to the inherent microglial-neuronal interactions including phagocytosis that occur in brain. While our microglia isolations were above the purity of another published microglial transcriptome study (Zhao et al, 2017), we cannot be certain that the higher expression of some of the typically neuronal genes were cell intrinsic to microglia rather than a result of increased neuronal phagocytosis in the MAA brain (Solga et al, 2015), although either explanation is of interest for understanding the pathogenesis. While the function of many of these neurotransmitter receptors on microglia is largely unknown (Schafer et al, 2013), their overall increase in expression following MAA suggests that microglia have altered sensitivity in the juvenile MAA brain.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…S1C) in our microglial isolations due to the inherent microglial-neuronal interactions including phagocytosis that occur in brain. While our microglia isolations were above the purity of another published microglial transcriptome study (Zhao et al, 2017), we cannot be certain that the higher expression of some of the typically neuronal genes were cell intrinsic to microglia rather than a result of increased neuronal phagocytosis in the MAA brain (Solga et al, 2015), although either explanation is of interest for understanding the pathogenesis. While the function of many of these neurotransmitter receptors on microglia is largely unknown (Schafer et al, 2013), their overall increase in expression following MAA suggests that microglia have altered sensitivity in the juvenile MAA brain.…”
Section: Discussionmentioning
confidence: 76%
“…One potential limitation of our study was a low level of neuronal contamination (0.2-2% in control versus 0.5-4% in MAA, Supporting Information Figure S1C) in our microglial isolations due to the inherent microglial-neuronal interactions including phagocytosis that occur in brain. While our microglia isolations were above the purity of another published microglial transcriptome study (Zhao et al, 2017), we cannot be certain that the higher expression of some of the typically neuronal genes were cell intrinsic to microglia rather than a result of increased phagocytosis of neurons in the MAA brain (Solga et al, 2015), although either explanation is of interest for understanding the pathogenesis.…”
Section: Maa Offspring Microglia Compared With Other Mia Modelsmentioning
confidence: 78%
“…In this study, Table S9), therefore these genes are pertinent specific biomarkers of microglial reaction for multiple disease conditions. Another study revealed that <0.5% of the detected genes differed between FACS isolated homeostatic microglia from WT and CX3CR1 1/GFP microglia (Solga et al, 2015). Another study revealed that <0.5% of the detected genes differed between FACS isolated homeostatic microglia from WT and CX3CR1 1/GFP microglia (Solga et al, 2015).…”
Section: Specific Markers Of Microglial Statesmentioning
confidence: 98%
“…SDF-1 operating through the CXCR4 receptor promotes optic glioma cell survival, such that CXCR4 inhibition reduces tumor growth in vivo . A more complete characterization of TAMs support of tumor maintenance has been performed using optimized RNA-sequencing methods 41,42 .…”
Section: Tams and Low-grade Gliomamentioning
confidence: 99%